2016
DOI: 10.1002/gcc.22379
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of SMARCB1 By miR‐206, ‐381 and ‐671‐5p is evident in a variety of SMARCB1 immunonegative soft tissue sarcomas, while miR‐765 appears specific for epithelioid sarcoma. A miRNA study of 223 soft tissue sarcomas

Abstract: Complete/partial loss of SMARCB1 nuclear-immunopositivity is characteristic of a certain subset of soft tissue sarcomas (STSs). Our previous work showed that oncomiRs-206,-381, and 671-5p could silence the SMARCB1 mRNA and protein expression and that they display significant overexpression in epithelioid sarcomas (ESs). MiR-765 was overexpressed too, but functionally was inactive in the silencing. In the current work, using quantitative PCR, we conducted a miRNA study of 51 ESs, 20 rhabdoid tumors (RTs), 20 sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…The study by Hasselblatt et al showed that SMARCB1 deletions were identified in 4/7 (57%) PDC cases by FISH, but only in 2/7 (29%) cases by multiplex ligation‐dependent probe amplification (MLPA), suggesting that FISH is a more sensitive method than MLPA in the context of large homozygous deletions of PDC. In addition, the study by Sápi et al showed that the FISH method detected the presence of deletions in 95% of epithelioid sarcoma cases, while MLPA only in 73% of cases. These findings further confirm our prior results showing high sensitivity of FISH studies to detect homozygous deletions in epithelioid sarcomas compared to MLPA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Hasselblatt et al showed that SMARCB1 deletions were identified in 4/7 (57%) PDC cases by FISH, but only in 2/7 (29%) cases by multiplex ligation‐dependent probe amplification (MLPA), suggesting that FISH is a more sensitive method than MLPA in the context of large homozygous deletions of PDC. In addition, the study by Sápi et al showed that the FISH method detected the presence of deletions in 95% of epithelioid sarcoma cases, while MLPA only in 73% of cases. These findings further confirm our prior results showing high sensitivity of FISH studies to detect homozygous deletions in epithelioid sarcomas compared to MLPA .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study found upregulation of miR-671-5p and miR-193a-5p in PDC with loss of SMARCB1 expression. 21 Prior studies on epithelioid sarcomas have also identified epigenetic silencing of SMARCB1 by functionally active miRNAs (miR-206, miR-381 and miR-671-5), 22,23 suggesting an alternative mechanism for loss of SMARCB1 expression in cases lacking genetic evidence of SMARCB1 abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in SMARCB1 are involved in several cancer types, implicating this event as a driver of these malignancies. 12 This results in a global alteration in chromatin remodeling that needs to be better understood to design targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Kohashi et al [15] and Sapi et al [17] both used miRNA expression profiling to distinguish ES from other SD-NRT; both studies identified different but not fully convergent patterns of miRNA expression in ES and RT. Although these studies shed some light on new mechanisms for SMARCB1 down-regulation, they did not inform on the biological origin of the tumors.…”
Section: Discussionmentioning
confidence: 99%